A global prevalence of turnover intention among doctors: a systematic review and meta-analysis - Jingjing Wang; Hui Lv; Qin Qin; Hui Jiang; Wenjie Ren; Noorsuzana Mohd Shariff (Scientific Reports)
Abstract Turnover intention (TI) among doctors is a critical issue in healthcare systems worldwide, as it can lead to workforce shortages, increased workload for remaining staff, and negatively impact patient care. This review aimed to explore the prevalence and determinants of TI among doctors, providing a comprehensive understanding of the factors influencing their turnover intentions. A systematic review was conducted using four electronic databases: PubMed, Web of Science, Medline, and Scopus. Studies published between January 2019 and December 2024 were included. Observational studies reporting the prevalence of turnover intention among doctors and meeting the inclusion criteria were selected for analysis. Two independent reviewers assessed the eligibility of each study, and relevant data were extracted and recorded. A random-effects meta-analysis was performed to evaluate the prevalence of turnover intention, with heterogeneity assessed using the I2. Subgroup analysis and meta-regression were conducted to examine variations in study-level characteristics. A total of 34 studies (involving 97,672 doctors) were included in this review. The overall prevalence of turnover intention among doctors was 39% (95% CI = 0.34–0.44). Those doctors with lower job satisfaction (OR = 0.484, 95% CI = 0.358–0.654) were more likely to express an intention to leave their current positions. However, the odds ratio for male doctors (OR = 1.251, 95% CI = 0.916–1.708) did not reach statistical significance. Approximately 39% of doctors reported turnover intention. Lower job satisfaction was identified as a significant risk factor for turnover intention among doctors, whereas male gender was not found to be a statistically significant predictor.